2016
DOI: 10.1111/vru.12419
|View full text |Cite
|
Sign up to set email alerts
|

Gadoxetate Disodium (Gd‐eob‐dtpa) Contrast Enhanced Magnetic Resonance Imaging Characteristics of Hepatocellular Carcinoma in Dogs

Abstract: Hepatocellular carcinoma is the most common primary hepatic tumor in dogs and is amenable to surgical resection in many cases. Unfortunately, overlap of sonographic findings between benign and malignant hepatic lesions typically requires more invasive diagnostic tests to be performed (e.g., biopsy for histopathology). The availability of a noninvasive diagnostic test to identify hepatocellular carcinoma would be beneficial. The use of a liver-specific magnetic resonance imaging (MRI) contrast agent such as gad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
14
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 21 publications
6
14
2
Order By: Relevance
“… 3 9 In study involving dogs, HCC and malignant nodules were hypointense under Gd-EOB-DTPA MRI during the hepatobiliary phase, compared with normal liver or benign lesion. 12 17 However, in the present study, RCEI of HCC showed no difference compared with that of benign tumour, including nodular hyperplasia and hepatocellular adenoma. In one study involving humans, the expression of OATP during the hepatocyte phase decreased with increasing HCC grade, corresponding to a decrease in Gd-EOB-DTPA enhancement of lesions.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“… 3 9 In study involving dogs, HCC and malignant nodules were hypointense under Gd-EOB-DTPA MRI during the hepatobiliary phase, compared with normal liver or benign lesion. 12 17 However, in the present study, RCEI of HCC showed no difference compared with that of benign tumour, including nodular hyperplasia and hepatocellular adenoma. In one study involving humans, the expression of OATP during the hepatocyte phase decreased with increasing HCC grade, corresponding to a decrease in Gd-EOB-DTPA enhancement of lesions.…”
Section: Discussioncontrasting
confidence: 78%
“… 13 The uptake of Gd-EOB-DTPA by hepatocytes peaked at 10 minutes after administration of Gd-EOB-DTPA. 12 Another study described that SI of the hepatobiliary phase peaked at 26 minutes after administration of Gd-EOB-DTPA. 16 However, several reports showed that SI of the hepatobiliary phase reached the plateau at 20 minutes after administration of Gd-EOB-DTPA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Primary hepatic neoplasms represent between 0.6 to 1.3% of canine tumors (PATNAIK; HURVITZ; LIEBERMAN, 1980) and constitute up to 21% of liver diseases, being hepatocellular carcinoma (HCC) the most common hepatic neoplasm in dogs (HIROSE et al, 2014;CONSTANT et al, 2016). Canine HCC is more recurrent in males, usually in animals older than 10 years (BURITICÁ; BARBOSA; ECHEVERRY, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Liver canine neoplasms represent between 0.6 to 1.3% of canine tumors (PATNAIK;HURVITZ;LIEBERMAN, 1980;PATNAIK et al, 1981a;TRIGO et al, 1982), being hepatocellular carcinoma (HCC) the most common hepatic neoplasm (HIROSE et al, 2014;CONSTANT et al, 2016). Despite there is no clear evidence of a gender-related incidence and breed predisposition, higher risk to HCC has been related in male dogs older than 10 years and Shih-Tzu (Patnaik et al, 1981;Hirose et al, 2014).…”
Section: Introductionmentioning
confidence: 99%